miRNA-182-5p promotes myogenic differentiation of C2C12 cells via the suppression of ZBTB7A - Zhang, Mengyuan; Wang, Yongheng; Shan, Shan; Liu, Siyu (Frontiers in Veterinary Science, 2025)
IntroductionSkeletal muscle possesses a significant regenerative capacity, which is largely mediated by myogenic satellite stem cells. MicroRNAs are known regulators of muscle development. miR-182-5p plays important roles in cell proliferation and migration in various cell types and pathologies. However, its specific role in myogenesis remains unclear. In this study, we elucidated the function of miR-182-5p in the differentiation of C2C12 myoblasts.MethodsWe evaluated the effects of overexpression and inhibition of miR-182-5p in C2C12 cells on its myogenic differentiation ability using Giemsa staining. We also determined the mRNA and protein levels of myogenic differentiation marker genes in these cells at different time points after the induction of differentiation in these cells. The target of miR-182-5p was predicted using bioinformatics tools and validated using luciferase reporter assay.ResultsOverexpression of miR-182-5p via mimic transfection promoted differentiation, while its inhibition by a specific compound attenuated this process. Furthermore, using bioinformatic prediction and validation via a dual-luciferase reporter assay, we identified zinc finger and BTB domain containing 7A (Zbtb7a) as a direct target gene of miR-182-5p during C2C12 myogenic differentiation.ConclusionOur findings indicate that miR-182-5p positively regulates C2C12 differentiation, partly via the suppression of Zbtb7a and suggest that appropriate miR-182-5p expression is essential for normal myogenesis.